Reducing Objectification Could Tackle Stigma in the COVID-19 Pandemic: Evidence From China - Chen, Youli; Jin, Jiahui; Zhang, Xiangyang; Zhang, Qi; Dong, Weizhen; Chen, Chun (Frontiers in Psychology, 2021)
Stigmatization associated with the COVID-19 is expected to be a complex issue and extend into the later phases of the pandemic, which impairs social cohesion and relevant individuals’ well-being. Identifying contributing factors and learning their roles in the stigmatization process may help to tackle the problem. This study quantitatively assessed the severity of stigmatization against three different groups of people: people from major COVID-19 outbreak sites, has been under quarantine, and healthcare workers; explored the factors associated with stigmatization within the frameworks of self-categorization theory and core social motives; and proposed solutions to resolve stigma. The cross-sectional online survey was carried out between April 21 and May 7, 2020, using a convenience sample, which yielded 1,388 valid responses. Employed with data analysis methods like multivariate linear regression and moderation analysis, this study yield some main findings: 1) those from major COVID-19 outbreak sites received the highest level of stigma; 2) factors most closely associated with stigmatization, in a descending order, are: objectification and epidemic proximity in autonomic aspect, and fear of contracting COVID-19 in controllable aspect; and 3) superordinate categorization is a buffering moderator in objectification-stigmatization relationship. These findings are important for further understanding of COVID-19 related stigma; and they can be utilized for develop strategies to fight against relevant discrimination and bias. Specifically, reinforcing superordinate categorization by cultivating common-ingroup identity, such as volunteering and donating for containment of the pandemic, could reduce objectification and thus alleviate stigma.